Strategic planning in human and organizational dynamic as a result of cognitive processes - Perea Rivera, Jóse Luis (2008)
The thematic one must like intention to approach the main processes of the management of the human resources in the organizations of production of goods and services (company, industry, institution) is of the public or deprived sector, that in its operational dynamics is present the psychological component. Also it treats his interrelation that under a systemic approach and in the global perspective towards the modernity of Century XXI within the agreement and the organizational change, serves as support in the systematization of the management; which it causes the consistency between the planning, the evaluation for aims of the continuous improvement, accreditation or certification of quality of his processes, and the pertinence with the demands of the social reality, economic and also political of the country.